2019
DOI: 10.1177/0959683619855959
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the thermal state of permafrost under climate warming in Central Yakutia

Abstract: The relevance of the problem under review is explained by the need to study the thermal response of permafrost to the modern climate change. Evolution of the thermal state of grounds has been studied with a view to evaluate the effects of modern climate warming on permafrost in Central Yakutia. The leading method to study this problem is the arrangement and performance of long-term monitoring observations of the permafrost thermal state that enable quantitative evaluation of the thermal response of upper perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The active layer thickness varied at the site between 2.4 and 2.8 m depending on the summer air temperature. Our earlier studies in similar settings (sites B-59/87 and B-1601) showed the formation of dry taliks, 20 to 30 m in thickness, in very dry sands (2-4%) [36]. Incipient water erosion features were observed on the slopes of the disturbed site.…”
Section: Water Pipelinementioning
confidence: 58%
See 2 more Smart Citations
“…The active layer thickness varied at the site between 2.4 and 2.8 m depending on the summer air temperature. Our earlier studies in similar settings (sites B-59/87 and B-1601) showed the formation of dry taliks, 20 to 30 m in thickness, in very dry sands (2-4%) [36]. Incipient water erosion features were observed on the slopes of the disturbed site.…”
Section: Water Pipelinementioning
confidence: 58%
“…The pipeline routes traverse areas with difficult surface and ground conditions, including the presence of continuous permafrost, suprapermafrost water, massive ground ice, and extensive taliks, as well as the widespread occurrence of frost-related landforms and processes [36,37]. In the study area, the permafrost terrains crossed by the pipelines include a floodplain, sand ridges comprising the middle alluvial terraces, and inter-alas terrain on the upland (Table 1).…”
Section: Study Area and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1987, observational studies have been conducted along the northern section of the Tommot-Yakutsk Railway to quantitatively assess the spatiotemporal changes in the thermal state of permafrost due to anthropogenic impacts [16][17][18][19][20][21].…”
Section: Observation Network and Methodologymentioning
confidence: 99%